Determining the severity of Plasmodium falciparum malaria in Ethiopia - Zinaye Tekeste; Meseret Workineh; Beyene Petros (Elsevier, 2013)
Summary: Background: In the majority of health centers in Ethiopia, the severity of falciparum malaria has been determined by parasitemia alone. However, it has been suggested that the use of peripheral infected RBC counts as an indicator of disease severity by itself is insufficient. Therefore, this study was performed to assess the severity of falciparum malaria infection in three Ethiopian localities with epidemic malaria and to compare the usual severe malaria determination technique (parasitemia) used in Ethiopia with other malaria severity determination parameters: circulatory collapse, cerebral malaria and severe anemia. Methods: Blood samples were collected from 400 individuals to examine the presence of falciparum malaria in the Awash, Metehara and Ziway areas of Ethiopia. Data on cerebral malaria, circulatory collapse and severe anemia were collected from 210 falciparum malaria patients. Results: Of the 400 individuals examined, 210 were positive for falciparum malaria, and 190 were negative and served as healthy controls (HC). Severe anemia (18 patients, 8.57%) and circulatory collapse (25 patients, 11.90%) were the common features associated with severe falciparum malaria. Additionally, the detection of severe malaria was comparable using parasitemia, circulatory collapse or anemia. Conclusion: The findings of this study demonstrated comparable capacity for detecting severe falciparum malaria using circulatory collapse, severe anemia or parasitemia. Therefore, in addition to parasitemia, assessing severity of falciparum malaria using circulatory collapse and severe anemia will facilitate the diagnosis and management of malaria in Ethiopia. Keywords: Severe anemia, Cerebral malaria, Circulatory collapse, Ethiopia